Evaluating the implementation of the mechanical engineering student skills competency - Galan Raditya Saputra; Mujiyono Mujiyono (Jurnal Pendidikan Vokasi, 2024)
This study aims to evaluate the implementation of the Expertise Competency Test (UKK) for students of Vocational High Schools (VHS) in the Machining Engineering Expertise Program implemented by the First Party Professional Certification Agency (LSP P1) in Banten Province. The evaluation was conducted using the CIPP model (Context, Input, Process, Product, and Outcome). This study is useful for assessing the performance of LSP P1 in implementing the UKK and evaluating the impact of UKK graduates on their acceptance in the industrial world. The research was conducted in three vocational schools in Banten Province with the research subjects including the head of LSP P1, the head of the machining engineering expertise programme, and competency assessors. The research instruments used were questionnaires, observations, documents and interviews, which had been validated by expert judgement. The data analysis technique used was descriptive quantitative. The results showed that the implementation of UKK by LSP P1 in Banten vocational schools received the following evaluations: (1) Context aspect scored 3.36 (very good category), (2) Input aspect scored 3.47 (very good category), (3) Process aspect scored 3.36 (very good category), (4) Product aspect scored 3.26 (very good category), and (5) Outcome aspect scored 2.94 (good category). In conclusion, the implementation of the UKK by LSP P1 in the Machining Engineering Expertise Programme at SMK Banten Province has been running very well in most aspects, although there is room for improvement in the Outcome aspect related to the impact of graduates in the industrial world. The contribution of this research is to provide an overview of the effectiveness of expertise competency certification in SMKs as well as input to improve the quality of graduates who are better prepared to compete in the world of work.